Secure Automated In-home Patient Monitoring - R. Suji Pramila; A. Shajin Nargunam; V. A. Tibbie Pon Symon (Highlights on Medicine and Medical Research Vol. 12, 2021)
In-home patient monitoring plays an important role in the early detection and prevention of diseases. This paper presents the design of a wireless sensor network to monitor the patient in his/her home. Different body sensors are fitted on the patient’s body to collect the body parameters like temperature, blood pressure, ECG and pulse rate. Currently, most of the monitoring systems use Personal Computer (PC) as a local database to store patient’s body parameters before sending them to the hospital. Here the need for a PC is eliminated by mobile phone. The body parameters collected by sensors are confidential and are securely forwarded to the hospital. A variation of Ciphertext Policy Attribute-Based Encryption (CP-ABE) with double encryption technique is used to achieve security. When a patient moves away from the home, outdoor monitoring is also supported by the mobile phone because the mobile phone is always carried by the patient. Hence the mobile phone is used as a local database, eliminates the need for a PC and supports outdoor monitoring. Finally, real-time monitoring is implemented with the help of a temperature sensor. The sensing circuit consists of a temperature sensor, Analog to Digital Converter (ADC), Microcontroller, LCD and Bluetooth device. The laptop is designed as a hospital server using the mhotspot tool. Temperature readings are automatically forwarded to the android mobile of the patient. Then it is forwarded to the laptop using Wi-Fi communication and an immediate response is given to the patient’s mobile phone.